PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN SINTANG - Andryani, Yuliana Tetean; Wahyudi, Wahyudi; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEducation is a determining factor in creating the nation’s progress. Teachers have a very important role in achieving educational goal, for that the teacher must have a good performance. There are many factors that influence teacher performance, some of them are Principal’s leadership and  Teacher Work Motivation.The purpose of this research was to find : The Influence of Principal’s Leadership and  Teacher Work Motivation on the Performance of State Junior High School Teachers in Kecamatan Sintang. The research uses a quantitative approach in the form of associative. This research was held on seven State Junior High School in Kecamatan Sintang with the sample 112 respondent. Analytical techniques used simple linear regression analysis techniques and multiple linear regression analysis techniques. Based on the results of study it can be seen that (1)there is a significant influence of the Principal’s Leadership on the Performance of State Junior High School Teachers in Kecamatan Sintang. (2) there is a significant influence of Teacher Work Motivation on the Performance of State Junior High School Teachers in Kecamatan Sintang. (3) there is a significant the Influence of Principal’s Leadership and  Teacher Work Motivation on the Performance of State Junior High School Teachers in Kecamatan Sintang. Keywords : Principal’s Leadership, Teacher Work Motivation and Teacher Performance.